International Student Migration and Polymedia: The Use of Communication Media by Bangladeshi Students in Germany - Md Matiul Hoque Masud (Research in Social Sciences and Technology- OpenED Network, 2020)
Tertiary-level students from Bangladesh usually migrate to Germany for the purpose of higher studies. These international student migrants use communication media to maintain connections with family members and friends in Bangladesh and social networks with friends, classmates, and Bangladeshi community members in Germany. Drawing on the experiences of Bangladeshi student migrants in Germany and using polymedia theory, this paper investigates how the migrant students use the polymedia environment to maintain the transnational social networks and connections. This paper is based on qualitative data derived from 18 in-depth interviews with Bangladeshi migrant students in Germany. Findings suggest that using the polymedia environment, Bachelor migrant students receive emotional support from their family members back home, while Masters and PhD students are responsible for providing emotional and practical support to their left-behind families, relatives, and friends. Migrant students’ media usage with families and friends living in Bangladesh is influenced by their marital status and gender as well as their familial and social structure in Bangladesh. Their use of communication media with the members of the Bangladeshi community and foreign classmates living in Germany is comparatively less frequent and more education-oriented.